2021
DOI: 10.1177/01945998211020302
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Tube Placement Following Transoral Robotic Surgery for Oropharyngeal Squamous Cell Carcinoma

Abstract: Objective To identify factors that may predict the need for feeding tubes in patients undergoing transoral robotic surgery (TORS) in the perioperative setting. Study Design Retrospective chart review. Setting Academic tertiary center. Methods A retrospective series of patients undergoing TORS for oropharyngeal squamous cell carcinoma (OPSCC) was identified between October 2016 and November 2019 at a single tertiary academic center. Patient data were gathered, such as frailty information, tumor characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Readmission due to electrolyte abnormalities or digestive issues was seen in 4.6% of this cohort. Consistent with other studies, we found that the majority of patients receiving TORS did not require feeding tube placement . Still, it may be beneficial to consider prophylactic measures to mitigate the risk of poor oral intake following TORS, such as routine assessment of preoperative and postoperative swallowing function to risk stratify patients, placement of temporary feeding tubes during the index admission for those with decreased laryngeal function, routine use of perioperative corticosteroids, or enrollment in Enhanced Recovery After Surgery pathways .…”
Section: Discussionsupporting
confidence: 87%
“…Readmission due to electrolyte abnormalities or digestive issues was seen in 4.6% of this cohort. Consistent with other studies, we found that the majority of patients receiving TORS did not require feeding tube placement . Still, it may be beneficial to consider prophylactic measures to mitigate the risk of poor oral intake following TORS, such as routine assessment of preoperative and postoperative swallowing function to risk stratify patients, placement of temporary feeding tubes during the index admission for those with decreased laryngeal function, routine use of perioperative corticosteroids, or enrollment in Enhanced Recovery After Surgery pathways .…”
Section: Discussionsupporting
confidence: 87%
“…When an NGT is placed, close postoperative coordination with the dietitian and SLP may expedite nutritional and swallowing recovery. 22,37 We observed higher G-tube rates and decreased removal probability in patients with higher baseline DIGEST grades and lower PSSHN-Diet and MDADI composite scores. These findings suggest that pretreatment swallowing dysfunction is associated with increased likelihood and duration of FT placement.…”
Section: Discussionmentioning
confidence: 68%
“…Institutional practices may change, as recent evidence suggests NGT placement during TORS may not be necessary. 22 Regardless, these results inform FT outcomes following this practice. When an NGT is placed, close postoperative coordination with the dietitian and SLP may expedite nutritional and swallowing recovery.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…If surgery is selected, a transoral approach should be preferred. Indeed, minimally invasive surgery (TORS and elective neck dissection or SNB) has demonstrated promising results in terms of swallowing function and could be an interesting option to avoid late side-effects of RT [74,75]. Several phase III clinical trials (Best Of and TORPHYNX; ClinicalTrials.gov Identifiers: NCT02984410 and NCT04224389, respectively) comparing TORS and RT in terms of swallowing function in patients with early-stage OPSCC are currently ongoing.…”
Section: Early-stage Opsccmentioning
confidence: 99%